The relationship between childhood maltreatment and social anxiety among Chinese male individuals with drug use disorders: a moderated mediation model of fear of negative evaluation and self-construals - Liu, Yang; Zhang, Hao; Miao, Hualing; Zhang, Jia; Guo, Cheng (Frontiers in Psychology, 2023)
Background Social anxiety (SA) is prevalent among individuals with drug use disorders, playing a significant role in the etiology and maintenance of drug addiction. The etiological model of SA suggests a link between the development of SA and childhood maltreatment. Childhood maltreatment not only acts as a complex trauma with negative effects on individuals’ selves and other cognitions but also exerts a negative influence through early negative parent–child interactions on individuals’ internal working models, leading to the development of fear of negative evaluation and SA. Furthermore, self-construals, as a personality trait that emerges from the framework of the theory of sociocultural models, may exert a moderating effect on these mechanisms. The present study utilized a moderated mediation model to examine how childhood maltreatment relates to SA in individuals with drug addiction, aiming to provide support for a comprehensive understanding and effective resolution of SA in this group. Methods A total of 618 Chinese male individuals with drug addiction (M = 34.13, SD = 8.76) participated, and they completed the Childhood Trauma Questionnaire Short Form, the Fear of Negative Evaluation Scale, the Self-Consciousness Scale’s Social Anxiety Subscale, and the Self-Construal Scale. SPSS PROCESS Macro was used to analyze the data. Result Correlation analysis revealed weak correlations among all variables but strong correlations between the SCS subscales. Mediation analyses revealed that fear of negative evaluation partially mediated the association between childhood maltreatment and SA. Moderated mediation analyses revealed that the link between fear of negative evaluation and SA was moderated by independent self-construal. The association was stronger among those with high independent self-construal than among those with low independent self-construal. An integrative moderated mediation analysis indicated that independent self-construal positively moderated the indirect association between childhood maltreatment and SA via fear of negative evaluation. However, interdependent self-construal did not show a moderated effect. Conclusion Fear of negative evaluation plays a partial mediating role in the relationship between childhood maltreatment and SA, while independent self-construal enhances the association between fear of negative evaluation and SA. Decreasing the fear of negative evaluation and intervening in self-construals may attenuate the association between childhood maltreatment and SA among Chinese male individuals with drug addiction.